Lanthanum carbonated-associated injury to the small intestine. Issue 11 (November 2015) - Khurram, Muhammad; Montgomery, Elizabeth
Abstract: Lanthanum carbonate (LC) is a phosphate binder that does not contain aluminium or calcium. It is used in patients with chronic renal insufficiency to treat hyperphosphataemia. Prolonged use of LC may lead to gastrointestinal mucosal injury. We report a case of a 76 year old male with history of end stage chronic renal disease status post transplant on peritoneal dialysis, treated with lanthanum carbonate. The patient had persistent vomiting and diarrhoea and underwent upper GI endoscopy. Gastric and duodenal biopsies obtained in 2010 showed changes that were reported as mucosal calcinosis. Upon re-review following the publication of a series of such patients in 2015, we noted prominent lamina propria histiocytes filled with mineral like material, with dense and granular deposits giving it a calcinosis like appearance in keeping with lanthanum carbonate. The patient had been on a protocol using lanthanum carbonate before it was approved by the Food and Drug Administration in the United States. The differential diagnosis of gastrointestinal histiocytosis should include lanthanum carbonate medication-associated injury in renal failure patients, further expanding the list of medications associated with gastrointestinal tract injury in patients with renal disease.